2013
DOI: 10.1039/c3cc38228a
|View full text |Cite
|
Sign up to set email alerts
|

Polymer dual ring resonators for label-free optical biosensing using microfluidics

Abstract: We demonstrate a polymer resonator microfluidic biosensor that overcomes the complex manufacturing procedures required to fabricate traditional devices. In this new format, we show that a gapless light coupling photonic configuration, fabricated in SU8 polymer, can achieve high sensitivity, label-free chemical sensing in solution and high sensitivity biological sensing, at visible wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…It has been shown that using visible wavelengths of light within a biosensor, the gap between the bus waveguide and ring resonator is below 100 nm in order to enable an efficient coupling of light [7]. Thanks to the racetrack configuration of the microrings used in this study, we maintain the optical performance of the structure while extending the tolerance of the fabrication process by increasing the values of the gap to around 1 µm.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been shown that using visible wavelengths of light within a biosensor, the gap between the bus waveguide and ring resonator is below 100 nm in order to enable an efficient coupling of light [7]. Thanks to the racetrack configuration of the microrings used in this study, we maintain the optical performance of the structure while extending the tolerance of the fabrication process by increasing the values of the gap to around 1 µm.…”
Section: Introductionmentioning
confidence: 94%
“…Along these lines, M Hiltunen et al [6] have nicely demonstrated a polymeric slot waveguide with an integrated Young interferometer at 633 nm wavelength. Moreover M. H. M. Salleh et al [7] have proved a dual disk resonator integrated with a microfluidic device at visible wavelengths. Although these studies are of tremendous importance, in their fabrication process for the master mould the structures were patterned by electron beam lithography followed by etching and anti-adhesion treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most analytes are aqueous with a large optical absorption loss at the lightwave band of 1550 nm [28], which greatly deteriorates the Q value of SOI-based MRs [3,29]. The polymer waveguides can work at the lightwave bands of 650 nm or 830 nm [30,31,32] where the aqueous analyte has a very low optical absorption loss [28]. Finally, in order to introduce and control the analyte sensed by MR, biosensors usually integrate microfluidic circuitry, forming optofluidic systems [5].…”
Section: Waveguide Design and Temperature Sensitivity Investigationmentioning
confidence: 99%
“…Microring resonators have been demonstrated on different optical materials such as silicon-on-insulator (SOI) [11], Si x N y [12,13], and polymers [14][15][16]. Compared with conventional inorganic materials, polymers as organic materials have advantages such as low cost, high optical transmittance, and simple fabrication processes [17,18].…”
Section: Introductionmentioning
confidence: 99%